Retraction Notice: A modified circulating current suppression control based on MMC grid connected using NLM - Hasan, H. A.; Chillab, Riyadh Kamil; Hannan, Ahmed K.; Farghly, Abdelrahman (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
-----------------------------------------------------------------------------------------------Notice of RetractionAfter careful and considered review by a duly constituted expert committee, this paper has been found to be in violation of IAES Publication Principles. 1. PlagiarismThe article was found to have copied portions of content from the following Chinese paper without appropriate citation:DOI: 10.13873/J.1000-9787(2024)11-0028-05https://d.wanfangdata.com.cn/periodical/Ch9QZXJpb2RpY2FsQ0hJTmV3UzIwMjUwMTE2MTYzNjE0Eg5jZ3FqczIwMjQxMTAwOBoIM3B4b2xsZ3M%3D 2. Authorship MisconductThe Editorial Office received a formal request from Dr. Riyadh Kamil Chillab (University of Baghdad), who stated: “as I was mistakenly included as an author without my consent.” This confirms that his name was added to the article without his knowledge or approval, constituting a serious violation of authorship ethics. 3. Corresponding Author’s StatementThe submitter of the paper, Mr. Ahmed Kamil Hannan, sent multiple emails to the Editorial Office regarding manuscript ID: 23942 (“A modified circulating current suppression control based on MMC grid connected using NLM”, Vol. 16, No. 2, June 2025, DOI: 10.11591/ijpeds.v16.i2.pp1051-1060).In his communications, Mr. Hannan did not acknowledge plagiarism. Instead, he stated that the authors had “noticed scientific errors in the manuscript” and requested withdrawal of the paper. He further offered to bear all costs and assured that the manuscript would not be submitted to any other journal. Retraction DecisionIn accordance with IAES’s commitment to uphold the highest standards of academic integrity, and considering both plagiarism and authorship misconduct, the content of this article has been formally retracted from the OJS platform.----------------------------------------------------------------------------------------------- High total harmonic distortion (THD) occurs when conventional circulating current suppression and modulation strategies fail to control arm circulating current in a modular multilevel converter (MMC) controlled by a virtual synchronous generator. This paper proposed a joint circulating current suppression technique that improves the proportional resonant controller's control mode and introduces the nearest level approach modulation (NLM) strategy for arm circulating current rectification. The MATLAB/Simulink program is used to conduct the simulations. The results show that: when the grid frequency does not fluctuate, the joint suppression strategy's arm current THD is 2.79%, 0.92% lower than the quasi-proportional resonant controller's (QPRC) THD; under primary frequency modulation, the suggested strategy's THD of the a-phase current is 1.75%, 1.03% lower than the QPRC's THD. Under typical operating conditions and with primary frequency management of the grid-type MMC, the results show that the proposed combined circulating current suppression technique may successfully lower total harmonic distortion (THD), eliminate bridge arm circulating current, and improve power quality.